Excel-database converting system using data normalization technique - Ahmad, R. (Springer Verlag, 2014)
This paper is intended to present an application system which can facilitate users in converting from Excel spreadsheet to database structure by using data normalization technique. It provides users with an automated system that can develop a database in its third normal form (3NF) from an Excel spreadsheet. There are two major problems of Excel spreadsheet that are emphasized in this project which are data redundancy and update anomaly. Prototyping-based methodology is used in order to develop this system. The system just creates the SQL codes for creating the database structure and populating the database; however, how the users make use of it such as interface for database interaction is not covered at this stage of project. Based on its functionalities, accuracy and performance, this system is able to bring more benefit and convenience for its users. Â© Springer Science+Business Media Singapore 2014.